'Snapshot': A Rural Team Ministry's Contribution to Mission in Changing Times. (2nd January 2019) - Truby, David
ABSTRACT: This article describes the life and work of the Wirksworth Team Ministry, a united benefice of ten churches with a market town and nine villages set in the Derbyshire Dales. It explores the strategy which helps to define the ways in which its churches relate both to their congregations and to their wider communities, seeking to build social and spiritual capital, concepts which have been described in the work of Peddle and Peters in Newfoundland. The idea of the churches contributing to a sense of place is examined along with the ways in which their congregations serve those communities. In conclusion, the article points to the range of possibilities for ministry at a time when inevitable change for rural parishes is being driven by national policy.